Location conditions of energy-intensive enterprises - Rüdiger Hamm (European Regional Science Association (ERSA), 2013)
There is an interdependent relationship between enterprises and the region in which they are located: On the one hand the conditions of this location influence turnover, costs, profits and thus the economic situation of the individual firm. On the other hand the economic situation of the regional firms is an important determinant of regional economic success and the wel-fare of the people living in that region. This happens directly because the firms stabilize regional income and employment; but there are also indirect effects running via income and input-output-linkages. Regional economic success and welfare in turn determine the regional tax receipts and the regions? possibilities for positively influencing the location conditions. These interdependencies give an explanation for the high interest firms, politicians and researchers normally have in regional location conditions and their quality. The better a region?s information about these issues, the better its possibilities to promote its location advantages and the more efficiently it can use its scarce financial means to reduce the locational disadvantages. Regional marketing and improvements of the region?s location conditions aim at the acquisition of new firms, at additional private investment in the region, at the creation and stabilization of employment and the population?s welfare. In recent years the Niederrhein Institute for Regional- and Structural Research (NIERS) has surveyed firms to thoroughly analyze the location conditions of Middle Lower Rhine Area ? a German region located in the western part of Northrhine-Westphalia. This research especially aimed at judging the location conditions? quality in Middle Lower Rhine Area. But as the firms had to evaluate not only the local quality but also the general importance of the location factors and as firms? participation in these surveys has been sufficiently high the results also give the opportunity to rank the location factors by its relevance and to differentiate this kind of analysis by industry. So, the aim of the proposed paper is twofold: It firstly describes which locational factors are ? on the basis of the above mentioned surveys ? most important from the firms? point of view. To find out whether energy-intensive industries have special location requirements it secondly compares these general results with those from energy-intensive industries.
Keywords: R12; 330; Location; location conditions; energy-intensive industries